PENGARUH POLA PEMBERIAN PAKAN TERHADAP KONSUMSI PAKAN, KECERNAAN NDF DAN ADF, PRODUKSI DAN KOMPOSISI SUSU PADA SAPI PERAH LAKTASI - Djodi Achmad Hussain Suparto (Sekolah Tinggi Manajemen IMMI, 2018)
This study was aimed at determining the effect of three ration dilevery pattern, namely Component Feeding (R0), Cafeteria Feeding (R1) and Feeding Total Mixed Ration (R2) on Dry Matter Intake, the digestibility of Neutral Detergent Fiber (NDF) and Acid Detergent Fiber (ADF), the milk production and composition (fat, protein, lactose, Solid Non Fat/ SNF).The material used were 15 primiparous lactating dairy cows in 3-8 months of lactation with the average body weight of 515 kg ± 61.5 kg, the cows were fed ration consisting 60% of forage (57% chopped Elephand grass, 3% Gleridiea) and 40% consentrate. The animals were randomly grouped in to three different feed delivery patterns, namely : Componen feeding (R0) (feed dilyvery of concentrates and forage orderly in a feed place at different time); Cafeteria feeding /Choice Feeding (R1) (feed delivery of concentrates and forage separately in a separate feed places at the same time); Total Mixed Ration/TMR (feed delivery of mixed forage and concentrates in a feed place at the same time). The study was experimental method using a Completely Randomized Design (CRD). The variables measured were Dry Matter Intake (DMI), NDF and ADF digestibilities, milk production and compositions. The data were analyzed with Analysis of Varian (ANOVA) and continued with Honest Significant difference between feed delivery treatments.The result showed the average DMI was 16.44 ± 1.2 kg/d; 16.74 ± 0.6 kg/d. and 16.20 ± 0.9 kg/d. NDF digestibility was 60.84 ± 3.6%, 63.41±1.4% and 64.90±3.9%; ADF digestibility 60.12 ±3.7%, 63.99±1.4% and 63.85 ±4.1%; Milk production was 11:04 ±2.72 kg/d, 12.52± 1.75 kg/d., and 11.72±2.44 kg/d. for R0, R1 and R2, respectively. The milk fat content was 3.61 ± 0.71%, 3.74±0.43%, 3.41± 0.19%; the milk protein content was 2.67±0.20%, 2.74 ± 0.12%, and 2.70±0.07%. The milk lactose content was 4.09±0.30%, 4.19±0.17%,4.18,± 0.06% while the milk SNF content 7.74±0.54%, 7,91±0.32%, and 7.80±0.18%, for R0, R1 and R2, respectively. The present study showed that the feed delivery pattern of Component Feeding, Cafetaria Feeding or TMR feeding did not effect (P0.05) DMI, NDF and ADF digestibility,milk production and composition of primiparous dairy cows.